2011
DOI: 10.3109/0142159x.2011.577119
|View full text |Cite
|
Sign up to set email alerts
|

Moving a formative test from a paper-based to a computer-based format. A student viewpoint

Abstract: From a student perspective, the computer was an acceptable platform for delivering a formative assessment comprising multiple choice questions (MCQs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Technical issues were also reported as a concern by students in other studies especially regarding Internet speed being a barrier for not completing online formative assessments 4 , 13 . Problems of academic dishonesty and their facilitation by technology have been reported before, 20 with higher probability of cheating occurring in e‐assessment in general 5 and summative e‐assessment in particular 21 . The reported perception in our study raises the need for adequate measures to ensure that summative e‐assessment is not jeopardized by acts of dishonesty.…”
Section: Discussionmentioning
confidence: 84%
“…Technical issues were also reported as a concern by students in other studies especially regarding Internet speed being a barrier for not completing online formative assessments 4 , 13 . Problems of academic dishonesty and their facilitation by technology have been reported before, 20 with higher probability of cheating occurring in e‐assessment in general 5 and summative e‐assessment in particular 21 . The reported perception in our study raises the need for adequate measures to ensure that summative e‐assessment is not jeopardized by acts of dishonesty.…”
Section: Discussionmentioning
confidence: 84%
“…We 7 and others 8 , 9 have compared paper‐based and computer‐based assessments in high‐stakes examinations and found that student acceptability of the latter was greater and preferred over a written format for important summative assessments of knowledge. In our previous study, 7 a major factor in this positive response was the students’ perception of fairness, though some students indicated that stricter controls to prevent cheating were required.…”
mentioning
confidence: 99%
“…The world scientific literature available (PubMed, Scopus, Embase, ProQuest, key words: computer-based assessment, e-assessment, students of medicine and health sciences, final examinations, years: 2000-2015, articles in English) included five publications devoted to opinions of students on participating in computer-aided exam [8][9][10][11][12]. Studies were conducted in New Zealand (2006, Faculty of Medicine, University of Otago) [8], the United Kingdom (2007, University of Bradford) [9], Saudi Arabia (2009, College of Medicine, King Abdulaziz University) [10], Germany (2011, Medical Clinic University of Heidelberg) [11], and Pakistan (2013, Dow University of Health Sciences International Medical College, Karachi) [12].…”
Section: Discussionmentioning
confidence: 99%
“…No information has been found about reliability of the research tools used to conduct the study in the available publications [8][9][10][11][12]. A pilot study on the opinions of students participating in computer-aided examinations at Warsaw Medical University was conducted, as well as an analysis of questionnaire reliability [14].…”
Section: Discussionmentioning
confidence: 99%